Global output of research on epidermal parasitic skin diseases from 1967 to 2017 - Waleed M. Sweileh (BMC, 2018)
Abstract Background Epidermal parasitic skin diseases (EPSD) occur in most countries and cause a considerable health and economic burden, particularly in the tropics and subtropics. The aim of this study was to assess and analyse peer-reviewed literature on EPSD in humans. The results of this study serve as an indicator of the extent the scientific community, health authorities, and international health agencies interact with EPSD as a health problem that is commonly associated with poverty and poor hygiene. Methods A bibliometric analysis methodology was used. The Scopus database was used to retrieve documents about EPSD for the study period (1967-2017). The study focused on scabies, tungiasis, pediculosis, hookworm-related cutaneous larva migrans (HrCLM), myiasis, and cutaneous strongyloidiasis. Documents that specifically and explicitly discuss EPSD in animals, aquatic organisms, and birds were excluded. Results In total, 4186 documents were retrieved. A fluctuated growth of publications on EPSD in the past five decades was found. The retrieved documents received 43 301 citations, an average of 10.3 citations per article and an h-index of 74. The keywords "scabies" and was the most commonly encountered keyword followed by the keywords "head lice" and "pediculosis". The most active journal involved in publishing articles on EPSD was the International Journal of Dermatology (164; 3.9%). Researchers from 93 different countries published the retrieved articles. The USA led with 735 (17.6%) documents, followed by the UK (274; 6.5%), and Germany (259; 6.2%). In terms of institutions, the Charité - Universitätsmedizin Berlin in Germany was the most active in this field with 78 (1.9%) publications, followed by the Universidade Federal do Ceará in Brazil with 52 (1.2%) publications. Conclusions Research on scabies and pediculosis dominated the field of EPSD research to the expense of tungiasis, HrCLM, myiasis, and cutaneous strongyloidiasis. There was an underrepresentation of literature from the tropics and subtropics despite EPSD being common in these areas. This could possibly be explained by the presence of limited number of non-English journals in the Scopus database. International research collaborations and research networking should be strengthened to help advance and prioritize research on EPSD.